Managing Conflicts to Ensure Smooth Organisational Functioning - Sharma, Vineet Kumar (Journal of Commerce and Trade, 2009)
Conflict is a process in which an effort is purposely made, by a person or a group, to offset the effort of another person or a group by some form of blocking that will result in frustrating the latter and attaining his or her goals or furthering his or her interests. Conflict is inevitable and often good, for example, good teams always go through a “form, storm, norm and perform” period. Getting the most out of diversity means often-contradictory values, perspectives and opinions. Conflict is not the same as discomfort. The conflict isn’t the problem - it is when conflict is poorly managed that is the problem. It is estimated that managers in various organizations spend 20% of their time in conflict resolution. Business houses spend a lot of time figuring out how to avoid conflicts from cropping up at all. Conflicts also arise due to confusion in the roles of the employees in an organization. Conflicts are not always unhealthy. A healthy conflict can lead to stimulating search for improved approaches to an existing system. Conflicts, once resolved, can lead to better final results. The main objective of this paper is to examine the cause, effects and the remedial actions taken to reduce conflicts in an organization.